Comparative Procedure Law - GILLES, Peter (Revista do Programa de Pós-Graduação em Direito, 2012)
The state of publications on comparative procedure law is still deficient and, accordingly, an understanding of the topic is only possible along very thin lines, which do not even include either accepted or rejected theories in the literature. In order to avoid any possible misconceptions, I would at this point like to emphasize, once again, the title and contents of this article: This article is not about presenting a certain comparative procedure law project or describing/outlin- ing so-called “concrete” comparative procedure law studies, but rather this article is focused on comparative procedure law in its theoretical-methodological context.